Opening address - Carter, David (New Zealand Science Review, 2010)
​It is a pleasure to open this Agri-Food Summit for the Riddet Institute.New Zealand has a proud history in agri-food going right back to the innovation of shipping frozen meat. Today the food and beverage sector generates over half of New Zealand’s export earnings and employs one in five of our working population. Given its importance, maintaining and improving the performance of this sector is essential to achieving the Government’s economic growth agenda.The world population continues to increase and we all need to eat. We also face limited global resources to produce food, which raises the importance of innovation and wise stewardship of resources like water, soil and carbon. This is both an opportunity and a challenge we must respond to.